Life cycle cost analysis on wind turbines - Puglia, Gloria (My University, 2013)
Wind power is considered one of the most promising renewable energy sources as increase during the last decades show. Important issues concerning the availability of wind power are its high investment and maintenance costs. The investment cost has a high price especially for offshore plans. The maintenance costs are a significant part of the total cost especially when during the life period of a wind turbine (WT) more failures than expected happen. In order to avoid unexpected failures and decrease the cost of maintenance some systems have been used to monitor the condition of specific components and control continuously the status of the turbine. Optimization of maintenance and research on new strategies to prevent the major failures it might be considered a solution to decrease costs and Life Cycle Cost (LCC) Analysis can be a fundamental tool to achieve a cost-effective maintenance for wind turbines and to obtain a more competitive electricity energy price from wind power source. The goal of this project is to compare cost-efficient maintenance strategies for on- and off-shore wind power system using LCC analysis approach as a tool for maintenance management. The comparison has been made by application studies which were selected during the way. The first one (WT1) is an offshore turbine, Vestas 112V, 3MW; the second one (WT2), is an offshore turbine, Haliade 150, 6MW and the last turbine (WT3) is onshore, V112, 3MW. Data used for the three wind turbines have been provided by Vattenfall. Three different strategies have been studied and the effect produced by the usage of Control Monitoring System has been analysed. The aim of this analysis is to show quantitative results that could quantify and give clear support to the value of Control Monitoring System (CMS). A comparison between the different types of turbines has been done in order to observe when a control monitoring system is more economical profitable and then the total life cycle cost decreases more. The comparison has been analysed for offshore and onshore WTs with same rating power and two offshore WTs with a different rating power. Sensitivity analysis has also been carried out considering different values of discount rate. For any chosen value the CMS proves to be profitable. Finally the results have been compared to those obtained in previous work from Reliability-Centred Asset Management (RCAM) research groups where the profitability of CMS has been analysed considering that part of unscheduled service is replaced by the scheduled one, and considering that part of corrective maintenance (CM) is substituted with a cheaper preventive maintenance (PM) during the usage of a CMS. Results show different values of reduction in CM and PM when a CMS is used. In this work has been shown that the 27,5% of the unscheduled service has to become scheduled to make CMS profitable while in the previous work the value was about 47%. Comparable results have been obtained in the sensitivity analysis where the value of discount rate has been changed from 0 to 10 to observe its effect on the LCC. The lower value of the discount rate the more efficient effect of CMS on LCC, the same result has been proved in the previous work. In RCAM’s work an entire offshore wind farm has been observed and LCC has been performed on the entire plant while in this thesis project 3 single WTs have been analysed. The comparison between these two works can be considered suitable since the used data are similar and the LCC analysis takes into account the same type of costs. An implementation that has been done in this work is the cost of production losses. This cost varies depending on the availability of the system and then it is affected by the efficiency of the CMS.
Keywords: Elkraftteknik; Electric power engineering